EVALUASI RASIONALITAS ANTI DIABETIK PASIEN RAWAT JALAN DIABETES MELLITUS TIPE 2 DI RUMKIT TK. IV 01.07.01 PEMATANGSIANTAR PERIODE APRIL – JUNI TAHUN 2024 - Chika Ade Hendranti; Elia Haloho; Emi Sugesti (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
Type 2 diabetes mellitus is a chronic disease caused by abnormalities in the process of insulin secretion, insulin resistance or due to unhealthy lifestyle factors, so there is a need for therapy to support the patient's quality of life. Rational antidiabetic therapy is one of the parameters of optimal therapy success for diabetic patients. The accuracy of therapy can be seen based on the patient's condition. This research was conducted at RUMKIT TK. IV 01.07.01 PEMATANGSIANTAR on patients with type 2 diabetes mellitus in 2024. The purpose of this study was to assess the profile of diabetic treatment and the rationality of antidiabetic therapy which includes 5 indicators of accuracy, namely the right indication, the right drug, the right dose, the PATIENT RIGHT, and the Exact delivery time. This research is non-experimental with a descriptive approach using prescriptions and medical record data. The results showed that out of 96 samples consisting of 71 women and 25 men, all of whom met the mixture of inclusion and exclusion, and showed that the predominant age prevalence was around 56-65 years (43,75%). In rational analysis recorded as having a potential indication of 100%, 100% correct medication, 100% correct dosage, 100% correct patient, 100% correct Exact delivery time each of which was processed using Microsoft Excel.